MANAJEMEN INFORMASI DAN KOMUNIKASI PENDIDIKAN ISLAM - Mochamad Nurcholiq (Ta`Limuna: Jurnal Pendidikan Islam, 2012)
The existence of information and communication in an education institution is a compulsosry. Because information functionate as connector between some sub organizations so it doesn’t isolate one another, but keeps as parts of main organization. Because of its important function, there are some experts who assume it as blood of organization, if the blood absence or doesn’t function the organization surely will die. It also with communication, it has significant in taking decision, applying policy for taking good result, solving the problems, and locating existing resources balance with the need and able to be taken advantage optimally.